1974
DOI: 10.1128/aem.27.4.744-747.1974
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase Activity of Anaerobic Organisms

Abstract: Anaerobic organisms were tested for phosphatase activity in different pH ranges. Several groups of organisms displayed characteristic patterns. Bacteroides fragilis, B. melaninogenicus, and B. ruminicola produced phosphatase with strongest activity at pH 8.6. Fusobacterium mortiferum was the only species of this genus to show strong hydrolysis. The enzyme was active in both acid and alkaline ranges. The activity of gram-positive organisms was variable, the most active groups being Clostridium perfringens, Pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

1977
1977
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Acid phosphatase activity appears to be a consistent property of CI. perfringens itself and, furthermore, Porschen & Spaulding (1974) obtained positive phosphatase reactions over a wide range of pH values. Whether this indicates one or several enzymes in CI.…”
mentioning
confidence: 83%
“…Acid phosphatase activity appears to be a consistent property of CI. perfringens itself and, furthermore, Porschen & Spaulding (1974) obtained positive phosphatase reactions over a wide range of pH values. Whether this indicates one or several enzymes in CI.…”
mentioning
confidence: 83%
“…Acid phosphatase test. Ueno et al 25and Porschen and Spaulding (20) reported that the ability of C. perfringens to produce acid phosphatase differentiated it from a number of other species of Clostridium. Blazevic and Ederer (2) described a test for phosphatase activity using phenolphthalein diphosphate as a substrate.…”
Section: Methodsmentioning
confidence: 99%
“…With the freshwater suspension, the recoveries after 24 h were approximately equal under both conditions; however, they were also about 23% lower than the respective recoveries at zero hour. The most likely explanation for these results is that (i) 20 to 30% of the C. perfringens population in the sewage sample were vegetative cells, (ii) because of factors in both sewage and seawater, they survive for periods up to 24 h in a sewage-sea- b Assay performed inside anaerobic tent.…”
Section: Fringensmentioning
confidence: 96%
“…Hydrolytic enzymes are produced by a number of species of anaerobic bacteria. These enzymes include hyaluronidase (12)(13)(14), chondroitin sulfatase (12)(13)(14), neuraminidase (8), heparinase (3,13), protease (12), elastase (12), collagenase (4,14), fibrinolysin (12), deoxyribonuclease (10), phosphatase (11,12), penicillinase (9,12), lecithinase (12), and lipase (12). There is some evidence that hydrolytic enzymes secreted by certain species of anaerobic bacteria play a role in the infectious process.…”
mentioning
confidence: 99%